On Fire Hazard of Lithium-Ion Batteries - A. R. Saklantiy; S. A. Larin; P. E. Pen’kovskii; E. M. Shagov (Теория и практика судебной экспертизы, 2025)
The article considers the basic mechanism and the construction details of lithium-ion batteries causing their fire and explosion hazard. It gives the results of fire-technical examinations carried out by RFCFS which confirm the possibility of fires due to the emergency operation mode of lithium-ion batteries. It is shown that use of an instrumental method for detection of the emergency operation traces left after fire on the battery fragments is not a sufficient reason to conclude that this operation mode caused the fire.